: Que narram os professores de uma Escola Municipal de Campo Grande sobre suas estratégias de ensino para aluno surdo - Marques, Pamela Krisia Yama Teixeira (Universidade Federal Rural do Semi-Árido, 2019)
The present work is the result of a research carried out in a primary school of themunicipal network of Campo Grande Rio Grande do Norte, this research has as centralobjective: to know which strategies are used by the teachers of the municipal network tothe deaf student in rooms of regular classrooms. Facing this objective, we chose thefollowing: Identify through the teachers' narratives strategies and methodologies usedby the teacher, aimed at the inclusion of deaf students through the literacy process. Theresearch is descriptive narrative, with a qualitative approach, having a bibliographical aswell as field study, using for the data collection interviews narrative of the teachers thatwere transcribed and soon after analyzed, narrative interviews were conducted withthree primary school teachers school. For the elaboration of the theoretical foundation,we use several scholars that approach the subject under study. Thus through reading itwas possible to identify that the literacy of deaf people in an inclusive perspective is achallenge faced by teachers of the regular classroom and one of the main barriers is thelack of interaction with the students who have deafness as well as the unpreparedness ofthese professionals referring to the Brazilian Sign Language. Therefore, inclusiveeducation must exist in all socio-educational contexts, providing a break in the bias stillexisting in the various spaces that treat people with Deafness in a prejudiced andsocially excluded way.
Keywords: Aluno surdo; Entrevistas narrativas; Ensino de LIBRAS; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS LIBRAS